Řešení spotřebitelských sporů v oblasti pojištění se zaměřením na komparaci soudního a vybraných způsobů mimosoudního řešení sporů - Škrobánková, Sabina (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2024)
Resolution of consumer disputes from insurance with focus on comparison of judicial and selected alternative dispute resolution methods Abstract The diploma thesis focuses on comparing judicial and alternative dispute resolution methods of resolving consumer disputes from insurance. Financial arbitration and the proceeding held by Office of the Ombudsman of the Czech Insurance Association were selected as alternative dispute resolution methods. The author characterizes these institutions and the court as the guarantor of the constitutionally guaranteed right to judicial protection. Furthermore, the work analyzes judicial and selected alternative dispute resolution methods in insurance disputes, with the consumer on one side, and on the other side, the insurance company or insurance intermediary. The individual proceedings before the selected institutions and the court are primarily analyzed from the perspective of the participants, especially consumers. The work is divided into four chapters, structured as follows: The first chapter defines key terms such as insurance, insurance contract and its parties, as well as other persons and entities involved in the contractual relationship, entrepreneur, consumers, and consumer disputes related to insurance. The chapter concludes with a brief typology of consumer...
Keywords: spotřebitel; pojištění; disputes; spory; consumer; insurance